Formalization of the process of the strategic adaptation of the manufacturing company to integration of complex-technical systems in the supply chain - Krykavskyi, Yevhen; Savchenko, Yuliia (Technology audit and production reserves, 2017)
The experience of functioning supply chains both in Ukraine and abroad convincingly proves the importance of a high level of synchronization of actions of all its participants. The formation of a successful model for managing these integrated structures underscores, at the same time, the exceptional importance of strategic harmonization of the goals of the chain and its participants. Despite the existence of a huge heritage of works devoted to the strategic aspects of the operation of such structures, research aimed at strategic adaptation of an individual participant to integration into the supply chain is clearly not enough. A consequence of the lack of a methodology for adapting an enterprise's strategy to integration into the supply chain is not only a lack of understanding by Ukrainian entrepreneurs of the potential benefits and threats of such integration, but also hostile to it. Thanks to the use of known strategic analysis tools such as SCOC and SWOT analysis, a scheme for identifying the motives for integrating a manufacturing enterprise into the supply chain of complex technical systems is proposed, which allows the enterprise to decide on the timeliness or, conversely, the relevance of such initiative. Taking into account the prioritization of the application of the project approach to the formation of the integration strategy of the supply chain, this allows to identify the impact of this strategy on the business strategy. In particular, for a manufacturing enterprise, this is considered within the framework of such strategic benchmarks as «efficiency» and «elasticity». In combination with the formation of corresponding sets of characteristic landmarks for each type of functional strategies, the formalization of the process of strategic adaptation of a separate manufacturing enterprise of complex technical systems to integration into the supply chain becomes possible in the context of the strategic goal set by the project. The practical value of such formalization lies in simplifying the decision-making process associated with the need to harmonize them with decisions of a higher level. And also with the choice of alternative options for filtering out those that contradict the main goal of the supply chain.